Two-dimensional magnetic materials of cobalt(ii) triangular lattices constructed by a mixed benzimidazole–dicarboxylate strategy. Issue 15 (26th March 2019) - Kong, Jiao-Jiao; Jiang, Yu-Xuan; Zhang, Jia-Chen; Shao, Dong; Huang, Xing-Cai
Abstract : Herein, three two-dimensional magnetic materials of cobalt(ii ) coordination polymers with triangular lattices were synthesized using a mixed benzimidazole–dicarboxylate strategy. Abstract : Frustrated spin systems, such as triangular lattices, are of significant interest in the field of chemistry, physics and materials science. However, the design and synthesis of these systems are difficult and have occurred serendipitously. Herein, we developed a straightforward and effective strategy for the design and construction of geometrically frustrated triangular lattices based on a mixed benzimidazole–dicarboxylate strategy. Using this method, we synthesized and characterized three Co II coordination polymers (CPs), namely [Co3 (1, 4-BDC)3 (5NO2 -BIm)2 (MeOH)2 ] n (1 ), [Co3 (1, 4-BDC)3 (5Cl-BIm)2 ]·2MeOH2 n (2 ), and [Co3 (1, 4-BDC)3 (5CH3 O-BIm)2 ]·2DMF n (3 ) (where 1, 4-BDC = 1, 4-benzenedicarboxylate, 5NO2 -BIm = 5-nitrobenzimidazole, 5Cl-BIm = 5-chlorobenzimidazole, 5CH3 O-BIm = 5-methoxybenzimidazole), with geometrically frustrated triangular lattices. Single-crystal X-ray diffraction studies revealed that the compounds1–3 exhibited two-dimensional (2D) layered structures formed by the linear trimeric Co3 secondary building units. The Co3 units exhibited an O h – O h – O h geometry in1 and mixed T d – O h – T d geometries in2 and3 . Interestingly, the triangular lattices of1–3 could be tuned by different benzimidazole derivatives; this resulted in the formation of distinct frustrated structures. Nitrogen adsorption–desorption isotherms indicated that the diverse Brunauer–Emmett–Teller (BET) surface areas of1, 2 and3 were 822, 877 and 943 m 2 g −1, respectively. Magnetic measurements indicated that1 showed the coexistence of long-range magnetic ordering and spin frustration, whereas2 and3 displayed a dominant frustration behavior. This simple synthetic method provides an alternative way for the design of frustrated triangular lattices.